(untitled) (Educação e Pesquisa, 2013)
When religion is converted in an integral part of modern political debates, religious ideas influence the decisions and definitions of concepts such as education, the participation in the labor market, the structure and function of the family as a social unit, and the equality. Integration and immigration come to the forefront as the concept of citizenship acquires culturalist and moralizing dimensions. Finally, religion, politics and education begin to interfere in the areas of life that belong to the private and public spheres. From our pedagogical perspective we understand that the educational lines marked by religion influence remarkably the future of many citizens, and attach themselves to the social-political realm. We thus become aware of the fact that religion as a powerful instrument of socialization exerts a strong influence upon citizens' education and values, and presents itself as the - normally hidden - social curriculum of the context closer to many citizens. The presence of Islam and of Muslims in Europe, though not a new phenomenon, is questioned by the nation-states, confronting the official curriculum and the regulated education, with the social curriculum, strongly influenced by Islam among its followers. It therefore converts itself in an integral part of the struggle for individual and collective national identity, be it with respect to laity, to democracy or to citizenship. And, in this sense, we would like to present an up-to-date review of this question so present in Europe today.